Antioxidant Activity of Tetrahydrocurcumins† - Venkateswarlu, Somepalli; V. Krishnaraju, Alluri; Sushruta, Koppula; V. Subbaraju, Gottumukkla (Asian Journal of Chemistry, 2010)
Tetrahydrocurcumins (4–6), obtained through the hydrogenation of naturally occurring curcumins (1–3), have shown weak antioxidant activity by superoxide scavenging ability and inhibition of lipid peroxidatio.